A systematic approach for early identification of Syphilis Infection among Men having Sex with Men in Chennai City: - A Page Rank Based Approach - Annadurai, Kabilan; Bagavandas, M (Indian Journal of Community Health, 2017)
Background: National surveillance conducted over 12 year period (2003 -2015) indicated that though the prevalence of HIV among Men having Sex with Men (MSM) has decreased in India, it is the second highest contributor in 2015. However, the prevalence of syphilis is an increase in the past 15 years. Under reach for screening; conscious hiding or withholding information due to stigma; limited resources and difficulty in screening vulnerable. Objective: The primary objective of the study is to explore the feasibility of using SNA for early identification of syphilis infection among MSM. Methodology: All MSM with newly identified syphilis infection in Chennai City during October and December 2015 were included in the study. A total of six samples were identified from the STI clinics lead by Government Hospitals in Chennai City, India and contact tracing at two levels (exponential snow-ball sampling method) were completed by the researcher. Unlike traditional screening program, the questionnaire used had indirect questions to avoid direct confrontation that helped to reach a total of 146 MSM during Jan to Oct 2016. Overall page ranking was completed for all MSM. All were followed up and encouraged to attend RTI/STI screening clinic through peers regularly. Results: 24 MSMs attended syphilis RPR screening test during this 10 months study period. 12 of 13 MSM were found to be positive for syphilis had page rank value of greater than one and 1 MSM had less than one page rank value. In the case of identified negative, all (n=11) except one MSM had page rank value less than one. Statistically, correlation of page ranking with syphilis reactive value showed a strong linear positive relationship (r = 0.732) with highly significance (p-value 0.000). Conclusion: This study proved that contact tracing and page ranking in SNA could be an effective measure to early identify syphilis infected MSM with its high positivity rate (54.2%).